Malaria vector feeding, peak biting time and resting place preference behaviors in line with Indoor based intervention tools and its implication: scenario from selected sentinel sites of Ethiopia. Issue 12 (December 2022) - Bedasso, Alemnesh Hailemariam; Gutto, Abebe Asale; Waldetensai, Abate; Eukubay, Araya; Bokore, Getachew Eticha; Kinde, Solomon; Gemechu, Fekadu; Debebe, Yared; Aklilu, Mesfin; Tasew, Geremew; Massebo, Fekadu; Teshome, Abebe; et al.
Abstract: In Ethiopia, malaria incidence has significantly reduced in the past decade through the combined use of conventional vector control approaches and treatment using antimalarial drugs. However, the sustainability of this achievement is threatened by the shift in biting and resting behaviors and emergence of insecticide resistance by the primary malaria vector. Therefore, continuous monitoring of the behaviour of malaria mosquitoes in different sentinel sites is crucial to design effective prevention and control methods in the local context. Entomological investigations were conducted in three sentinel sites for five consecutive months during the major malaria transmission season. The species composition, population dynamics, biting and resting behaviours of malaria vectors were determined using center for disease control and prevention (CDC) light trap, human landing catch (HLC), pyrethrum spray catch (PSC) and Pitfall shelter collection (PFS). Accordingly, 10 households for CDC, 10 households for PSC, 10 households for PFS and 5 households for HLC from each site were randomly enrolled for mosquito collection. A total of 8, 297 anopheline mosquitoes were collected from the three sites, out of which 4, 525 (54.5 %) were An. gambiae, s.l. 2, 028 (24.4 %) were An. pharoensis, 160 (1.9 %) were An. funestus and the rest 1, 584 (19 %) were other anophelines ( An. coustani, An. cinerus and An. tenebrosus ). No significant variation (P = 0.476) was observed between indoor (25.2/trap-night and outdoor collections (20.1/trap-night). Six hundred seventy six (43.3%) of An. gambiae s.l. (primary vector) were collected between 18:00 and 22:00 h. Biting activity declined between 00:00 and 02:00 h. The national malaria control program should pay close attention to the shifting behavior of vector mosquitoes as the observed outdoor feeding tendency of the vector population could pose challenges to the indoor intervention tools IRS and LLINs. Abstract : Malaria; An. gambiae ; Biting behavior; Resting behavior; Ethiopia.